Peningkatan Usaha UMKM Kantin Yen Yen melalui Digital Marketing dan Pencatatan Keuangan - Santi Rimadias; Andrew; Valent Tansuri; Nicho Febrianto; Aaron Christian; Kevin Timothy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Digital marketing and financial recording play an important role in improving MSMEs. Many MSMEs have good quality products and services, but their businesses are not profitable. This is due to the lack of application of digital marketing and still doing traditional financial records in their business. One of the MSMEs that we observed, namely the Yen Yen Canteen, had this problem. Therefore, our group conducted a service by helping to create social media and teaching application-based financial recording. After we did this service, the Yen Yen Canteen had social media and its content and made financial records through the application.